MECHANISMS FOR ENSURING THE QUALITY OF NORMATIVE LEGAL ACTS AT THE STAGES OF NORMATIVE CREATIVITY - Islomov Durbek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the main stages of rulemaking (norm-making) activity based on the Law of the Republic of Uzbekistan “On Normative Legal Acts.” In particular, it examines the legal mechanisms for planning, initiating, drafting normative legal acts, conducting regulatory impact assessment, legal and anti-corruption expertise, public discussion, coordination, and adoption of normative legal acts. The article also highlights practical challenges arising at different stages of the rulemaking process and proposes directions for improving the effectiveness and quality of norm-making activities.